Efeitos da variação no grau de correspondência regras/contingências sobre o comportamento de seguir regras - PINTO, Rafael Falcão Silva (Universidade Federal do Pará, 2014)
Literature has suggested that rules may generate responding patterns that are more resistant to changes in the reinforcement contingencies, and that the degree of resistance to change depends on the strength of the established relation between antecedent and consequent stimului. The present study investigated if an experimental history of weakening of the rule/programmed consequences relation would diminish the resistance to change of the rule-following operant when it was subjected to extinction. Ten undergraduate students were exposed to a matching-to-sample procedure. In each trial the participant was presented with a stimulus arrangement of a sample stimulus and tree comparison stimuli, and he/she should point the three comparison stimuli in a given sequence. Each comparison stimulus had one dimension (color, thickness or shape) in common with the sample stimulus and differed in the other two. The experiment consisted of two conditions, each having six phases differing in the order of presentation of the degrees of rule/contingency correspondence. In both conditions Phase 1 was initiated with minimal instructions and aimed at identifying if the participants had eventual preferences for any particular sequence. Phase 2 was initiated in both conditions with the presentation of instructions that were inconsistent with the prevailing contingencies. In Condition 1 Phases 3, 4 and 5 were initiated with instructions varying in their degree of correspondence with the programmed contingencies by 100%, 50% and 0% respectively. In Condition 2 the degree of correspondence with the contingencies for Phases 3, 4 and 5 were 0%, 50% and 100% respectively. In both conditions Phase 6 were initiated with inconsistent instructions. The participants‟ responses were reinforced with points which were exchanged by money in a continuous reinforcement schedule. All participants followed instructions in all phases of both conditions. These results suggested that manipulating the degrees of rule/programmed consequences correspondence was not a sufficient to produce behavioral change, i.e. it was not sufficient to make the rule/contingencies discrepancy more salient, thus leading to abandonment of rule-following behavior.